Studi tentang Pembiayaan Pendidikan Sekolah Dasar - Nanang Fattah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Study on Educational Costs in Elementary Schools. The purpose of this study was to investigate the effect of educational cost on the educational quality. A descriptive analytic approach was applied in this study. Data were gathered by questionnaire, interview, observation, and documentary study in all Public Elementary Schools in Kabupaten Bandung. The data were then analyzed qualitatively and quantitatively by correlation and regression. It could be concluded from data analyses that the cost had a little impact upon educational quality improvement in elementary schools. The were some components of cost significantly contributing to the learning-teaching process and to the quality of learning outcomes.